2008
DOI: 10.2147/vhrm.s1940
|View full text |Cite
|
Sign up to set email alerts
|

High density lipoprotein cholesterol: an evolving target of therapy in the management of cardiovascular disease

Abstract: Since the pioneering work of John Gofman in the 1950s, our understanding of high density lipoprotein cholesterol (HDL-C) and its relationship to coronary heart disease (CHD) has grown substantially. Numerous clinical trials since the Framingham Study in 1977 have demonstrated an inverse relationship between HDL-C and one's risk of developing CHD. Over the past two decades, preclinical research has gained further insight into the nature of HDL-C metabolism, specifi cally regarding the ability of HDL-C to promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 143 publications
(154 reference statements)
2
13
0
2
Order By: Relevance
“…The HDL increase observed in this study was similar to that reported in previous studies in both time and magnitude (Hatsukami et al, 2005). The rise of HDL levels of 5 mg/dL (approximately 8%) for the EHCSS-K6 group in the present study is within the reported 5-15% range typically reported with the use of statins for reducing CVD risk (Kapur et al, 2008). This increase may represent a beneficial shift, since there is evidence to support a 2% decrease in CVD risk for every 1 mg/dL increase in HDL levels (Kapur et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The HDL increase observed in this study was similar to that reported in previous studies in both time and magnitude (Hatsukami et al, 2005). The rise of HDL levels of 5 mg/dL (approximately 8%) for the EHCSS-K6 group in the present study is within the reported 5-15% range typically reported with the use of statins for reducing CVD risk (Kapur et al, 2008). This increase may represent a beneficial shift, since there is evidence to support a 2% decrease in CVD risk for every 1 mg/dL increase in HDL levels (Kapur et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…The rise of HDL levels of 5 mg/dL (approximately 8%) for the EHCSS-K6 group in the present study is within the reported 5-15% range typically reported with the use of statins for reducing CVD risk (Kapur et al, 2008). This increase may represent a beneficial shift, since there is evidence to support a 2% decrease in CVD risk for every 1 mg/dL increase in HDL levels (Kapur et al, 2008). These results support previous findings that switching from CC to smoke an EHCSS may alter lipid profiles in a favorable manner even when smokers increased the number of cigarettes smoked (Roethig et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…5A). The increase of metabolic gene expression has strong indication of anti-diabetic effects (Kapur et al, 2008). Meanwhile, after Danshen gavage, the expression of FAS was reduced by $65%, the expression of UCP-1, and UCP-2 increased 2-3 fold, strongly indicating decrease of fatty acid synthesis and increase of fatty acid oxidation.…”
Section: Danshen and Sanqi Regulate Metabolic Genes In Different Mannermentioning
confidence: 99%
“…Hyperlipidemia, characterized by high levels TG and TC in blood (Table 1), contributes to the development of IR and type II diabetes (Tang et al, 2011) Danshen alone slightly decrease TC, LDL-C and TG without significant difference (Table 1). Danshen significantly increase HDL-C, the "good cholesterol" which lower the risk of cardiovascular diseases (Kapur et al, 2008;Elshourbagy et al, 2014) In contrast, Sanqi alone significantly decreased serum TG levels, without significant effects on TC, LDL-C and HDL-C (Table 1). These data indicated that Danshen and Sanqi have different function on sugar and lipid metabolism.…”
Section: Dan-qi Treatment Significantly Improved Metabolic Health Of mentioning
confidence: 99%
See 1 more Smart Citation